2009
DOI: 10.1890/08-1560.1
|View full text |Cite
|
Sign up to set email alerts
|

Community‐level consequences of mycorrhizae depend on phosphorus availability

Abstract: Abstract. In grasslands, arbuscular mycorrhizal fungi (AMF) mediate plant diversity; whether AMF increase or decrease diversity depends on the relative mycotrophy in dominant vs. subordinate plants. In this study we investigated whether soil nutrient levels also influence the ability of AMF to mediate plant species coexistence. First, we developed a conceptual model that predicts the influence of AMF on diversity along a soil nutrient gradient for plant communities dominated by mycotrophic and non-mycotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 52 publications
11
77
0
2
Order By: Relevance
“…O alto nível de fósforo nas áreas estudadas pode ter influenciado negativamente a ocorrência dos FMA, prejudicando a colonização e a produção de glomerosporos. Em geral, solos com baixo nível de P (<40 mg dm -3 ) são mais ricos em espécies de FMA (Souza et al 2003;Collins & Foster 2009) e naqueles com concentração de fósforo >40 mg dm -3 a esporulação e a diversidade de FMA são negativamente afetados (Souza et al 2003;Hijri et al 2006;Gai et al 2009). …”
Section: Resultsunclassified
“…O alto nível de fósforo nas áreas estudadas pode ter influenciado negativamente a ocorrência dos FMA, prejudicando a colonização e a produção de glomerosporos. Em geral, solos com baixo nível de P (<40 mg dm -3 ) são mais ricos em espécies de FMA (Souza et al 2003;Collins & Foster 2009) e naqueles com concentração de fósforo >40 mg dm -3 a esporulação e a diversidade de FMA são negativamente afetados (Souza et al 2003;Hijri et al 2006;Gai et al 2009). …”
Section: Resultsunclassified
“…In line with this, it has been observed that AMF from less intensively managed sites are more beneficial for plant biomass production than AMF from sites of higher management intensity (Johnson, 1993;Singh et al, 2008b). However, it must be remembered that the beneficial effects of AMF decrease with increased nutrient fertility (Kiers & van der Heijden, 2006;Collins & Foster, 2009) and AMF may actually reduce plant growth at high fertility as a result of carbon loss (Smith et al, 2009). Moreover, some crops (e.g.…”
Section: New Phytologistmentioning
confidence: 88%
“…Studies on AM species dependency, the weighted difference in dry weight biomass of a plant in the presence and absence of mycorrhizas, have revealed that C 4 grasses are considerably more responsive to AM fungi than C 3 grasses Harnett, 1997, 1998). Additionally, Collins and Foster (2009) were able to establish AM-free and AM-inoculated mesocosms of adequate size to address community shifts in abundance of grasses. Their targeted experimentation revealed a decline in abundance of C 4 grasses in the AM-free mesocosms with a concomitant increase of C 3 grasses (Collins and Foster, 2009).…”
Section: Plant Community Level Shiftsmentioning
confidence: 99%
“…Additionally, Collins and Foster (2009) were able to establish AM-free and AM-inoculated mesocosms of adequate size to address community shifts in abundance of grasses. Their targeted experimentation revealed a decline in abundance of C 4 grasses in the AM-free mesocosms with a concomitant increase of C 3 grasses (Collins and Foster, 2009). This shift may be one example of a more generalized change toward plants that respond positively in terms of growth.…”
Section: Plant Community Level Shiftsmentioning
confidence: 99%